Impact-induced sublimation drives volatile depletion in carbonaceous meteorites - Zheng-Yu Long; Frederic Moynier; Tim F. J. Bögels; Linru Fang; Razvan Caracas; Marine Paquet; Fred Jourdan; Tu-Han Luu; Dimitri Rigoussen; Kun-Feng Qiu; Jun Deng; James M. D. Day (Nature Communications)
Abstract Carbonaceous chondrites are amongst the most chemically primitive solid materials in the Solar System, yet many are depleted in moderately volatile elements. Here, we report enrichments in heavier zinc isotopes in heated carbonaceous chondrites compared to the typical ranges for chondritic meteorites. Our results indicate that impact-driven thermal metamorphism under low-pressure conditions led to partial sublimation of zinc. First-principles calculations support that zinc escapes from solids in the absence of melting, consistent with shock heating and rapid outgassing. The resulting solid residue is strongly enriched in heavier Zn isotopes with minimal recondensation. These findings link extreme isotopic signatures to collisional processing, revealing that asteroid-scale impacts can drive volatile loss from undifferentiated asteroids. These carbonaceous chondrites provide the first unequivocal evidence for purely kinetic Zn isotope fractionation during volatilization. Impact-induced volatilization drives volatile depletion in asteroidal parent bodies, with implications for the delivery and distribution of volatiles in early planetary systems.